Communication Skills of Deaf Children - Rani Nur Umah; Mita Angraeni; Usman Usman; Fitriyani Fitriyani (Education Achievement: Journal of Science and Research, 2024)
As social beings humans have a main need, namely communication, basically communication is a process, and the process must have an obstacle. Like the barriers experienced by deaf children, they experience barriers in their hearing as a result of which deaf people have difficulty speaking so that deaf children are not or less able to communicate verbally. Deaf children maximize their sense of sight as a way to complete the lack of hearing. The purpose and benefits of this study are to determine communication skills in deaf children, know how to socialize deaf children, and find out what are the obstacles in communicating deaf children. This study also aims to test whether there is an interaction between two independent variables that affect verbal and nonverbal communication skills in deaf children.deaf people often have communication problems as in students at SLB B-C Wijaya Kusumah, they still have difficulty in communicating even though generally deaf people use sign language alternatives. The results of our research found that the communication skills of deaf children in SLB B-C Wijaya Kusumah are still very low, this was obtained from the results of the researcher's interview with the class teacher concerned. There are only two children out of nine children who have comprehension in communicating using sign language, the rest still need special guidance in order to maximize their sense of sight as a way to perfect communication.